(untitled) (Journal of Health Sciences, 2016)
Introduction: We can define extracranial carotid artery aneurysm (ECAA) as bulb dilatation greater than 200% of the diameter of the internal carotid artery (ICA) or in a case of common carotid artery (CCA) greater than 150% of the diameter. Surgical intervention is required for the treatment of this disease.Case report: This study presents an open vascular surgical procedure to resolve ECAA. We report a case of 61 years old woman with an extracranial internal carotid artery berry aneurysm, presented with a headache and dizziness when turning the head aside. Classic open surgery was performed and the lumen of berry aneurysm was separated with three clips from the lumen of ICA.Conclusions: The open surgical approach is the method of choice for the treatment of extracranial internal carotid artery pathological conditions.